Urgensi Manajemen Pendidik Lembaga Pendidikan Anak - Salim, Ahmad (Universitas Alma Ata, 2012)
Early childhood education has been developing in Indonesia. It needs professional teacher to accomplish the stated goals. To make professional teacher of early childhood education absolutely needs management. In this paper, writer would present the early childhood education teacher management especially in private early childhood education due to it has many problems. Management of teacher in early childhood education is started from identification of teacher qualification and quantity, developing and enrichment the teacher quality by make clear status of teacher, also increasing the teacher revenue/fee. Moreover the leader of early childhood education should manage retiring of the teacher. Writer believes that many steps above could develop quality of early childhood education. Keywords: Management, early childhood education, professional teacher,